Vibrational analysis and electronic properties of 2-Decenoic acid and its derivative by first principles. Issue 6 (2011) - Dwivedi Dwivedi, Apoorva Apoorva; Pandey Pandey, Anoop Kumar Anoop Kumar; Misra Misra, Neeraj Neeraj
Abstract : Royal jelly is the mixture of acids like 2-Decenoic acid (DA), 10-Hydroxy 2-Decenoic acid and many others. 10-HDA possesses strong inhibition to the growth of cancer cells, namely transferable AKR leukaemia, TA3 breast cancer, etc. The equilibrium geometry of 2-Decenoic acid and its derivative 10-Hydroxy 2-Decenoic acid in the ground state have been determined and analyzed by Density functional theory (DFT) employing 6-311 G (d, p) as the basis set. The harmonic frequencies of 2-DA and 10-HDA have also been calculated to understand its complete vibrational dynamics. The study of simulated spectra provides important information about the ability of the computational method to describe the vibrational modes.